Cross-correlation analysis of inner-leaflet-anchored green fluorescent protein co-redistributed with IgE receptors and outer leaflet lipid raft components. - Pyenta, P S (2001)
To investigate the structural basis for membrane interactions that occur between Lyn tyrosine kinase and IgE-Fc(epsilon)RI or other components of lipid rafts, we prepared a green fluorescent protein analog of Lyn (PM-EGFP) and used cross-correlation analysis to quantify co-redistributions of aggregates that occur after IgE-Fc(epsilon)RI is cross-linked on the cell surface. PM-EGFP, which contains minimally the palmitoylation and myristoylation sites on Lyn, was compared with another inner leaflet probe, EGFP-GG, which contains a prenylation site and a polybasic sequence similar to K-ras. Confocal fluorescence microscopy was used to examine co-redistributions of these inner leaflet components with IgE-Fc(epsilon)RI and outer leaflet raft components, ganglioside GD1b and glycosylphosphotidylinositol-linked Thy-1, under conditions where the latter were cross-linked externally to form large patches at the cell surface. The cross-correlation analysis was developed and characterized with simulations representing cell surface distributions, and parameters from the cross-correlation curves, rho(o) (peak height) and A (peak area), were shown to be reliable measures of the extent of co-redistributed aggregates and their size. Cross-correlation analysis was then applied to quantify co-redistributions of the fluorescently labeled inner and outer leaflet components on RBL-2H3 cells. As visually observed and parameterized in this manner, PM-EGFP was found to co-redistribute with lipid rafts significantly more than EGFP-GG or an endogenous prenylated protein, Cdc42. These quantitative results are consistent with previous analyses of Lyn co-redistributions and support the hypothesis that the functionally important interaction of Lyn with cross-linked IgE- Fc(epsilon)RI is due to their mutual co-association with lipid rafts.